(untitled) (Tạp chí Y học Cộng đồng, 2025)
Objective: To describe the clinical and radiographic characteristics of patients with unilateral mandibular condylar fractures. Subjects and Methods: This prospective descriptive study included 40 patients aged 16 years and older with unilateral mandibular condylar fractures who underwent open reduction and internal fixation. Participants were recruited using convenience sampling from July 2024 to April 2025 at the Department of Maxillofacial Surgery, National Hospital of Odonto-Stomatology, Ho Chi Minh City, and Military Hospital 175. Results: Among the 40 patients with unilateral mandibular condylar fractures, males accounted for 75%, with traffic accidents as the leading cause (92.5%). Clinically, preauricular tenderness was present in 85% of cases, limited mouth opening in 80%, and malocclusion in 70%. Radiographically, fractures on the posterior condylar process (52.5%) and subcondylar region (55%) were most common. Isolated condylar fractures represented 15% of cases, while the majority (85%) had associated mandibular fractures, most frequently involving the symphysis (52.5%). According to displacement classification, 52.5% of fractures were classified as type II, and 35% were classified as type III. Conclusion: The study highlights the predominance of traffic-related trauma and the high incidence of type II and III displacements in unilateral mandibular condylar fractures. These findings enhance current understanding of injury distribution patterns and provide a basis for selecting appropriate treatment approaches tailored to fracture characteristics.